Penanaman Pendidikan Karakter Melalui Pengelolaan Bank Sampah di Lingkungan Sekolah - Wina Maryuni, Ni Putu (Metta : Jurnal Ilmu Multidisiplin, 2024)
This research reveals the importance of instilling character education to every learner at every level through the Waste Bank. Waste Bank is one of the media in instilling two of the eighteen character education values of the Ministry of Education and Culture, namely creative and environmental care. This research uses a qualitative approach with a descriptive research type. Data were obtained through literature studies collected by tracing articles, reading literature, and analyzing research results. The results showed that the presence of Waste Bank in schools is expected to provide fresh air in the world of education, especially in instilling environmental and entrepreneurial character education in students. It is hoped that the Waste Bank will contribute to the independence of students to manage waste in their community environment.Planting entrepreneurial character from an early age is also very important so that students have a mentality of job creators instead of job seekers. Therefore, the main challenge is for authorities and stakeholders to coordinate and facilitate educational institutions to create a sustainability-based education system to create creative and environmentally-conscious outputs of prospective entrepreneurs given the mountains of waste in various parts of Indonesia.